2017
DOI: 10.1080/10495398.2017.1348357
|View full text |Cite
|
Sign up to set email alerts
|

Effects of MicroRNA-27a on Myogenin Expression and Akt/FoxO1 Signal Pathway during Porcine Myoblast Differentiation

Abstract: Skeletal myoblast differentiation is controlled by a multitude of transcription factors and signal pathways. Myogenin is a critical transcriptional regulator in the initiation and maintenance of myoblast differentiation. The Akt/FoxO1 signal pathway plays an important role in myoblast differentiation. MicroRNAs are a kind of small noncoding RNAs that have been regarded as important regulators in skeletal muscle cell proliferation and differentiation. The objective of this study was to investigate the effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…The modulation of FoxO1 involves in Akt (Zhang et al., 2018) and AMPK (Liu et al., 2018) pathways. We thus evaluated the expression of the proteins in these pathways.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The modulation of FoxO1 involves in Akt (Zhang et al., 2018) and AMPK (Liu et al., 2018) pathways. We thus evaluated the expression of the proteins in these pathways.…”
Section: Resultsmentioning
confidence: 99%
“…FoxO1 has been reported to be modulated by Nrf2 and SIRT1 signaling pathways (Lee and Goldberg, 2013; Gille et al., 2019). FoxO1 is involved in various pathways, including Akt (Zhang et al., 2018) and AMPK (Liu et al., 2018) pathways. We demonstrated that propofol reversed the elevated phosphorylation level of Akt and AMPK pathways induced by OGD/R in H9c2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…For example, treatment of melengestrol acetate increases myogenin mRNA expression in C2C12 cells, but no affect is observed in bovine muscle satellite cells ( 23 ) . miR-27a has the opposite role on differentiation between C2C12 cells and porcine myoblasts ( 24 , 25 ) . Therefore, study on role of leucine in porcine myoblast differentiation is absolutely essential.…”
mentioning
confidence: 99%
“…In PSCs in skeletal muscle miR-22 inhibits the proliferation through targeting the cyclin D1, cyclin B1, and p21 but promotes the differentiation through regulating the expression of MyoG and MyHC [61]. Further, miR-27a inhibits the expression of MyoG and it also regulates the protein kinase B/forkhead box protein O1 (Akt/FoxO1) signal pathway during porcine myogenesis [75] while miR27b acts to promote PSCs myogenesis by targeting MyoD family inhibitor (MDFI) [76]. Besides, mi-34c, inhibits PSCs proliferation and promotes PSCs differentiation.…”
Section: Role Of Mirnas In Myogenesismentioning
confidence: 99%